2022
DOI: 10.3390/app12157864
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Relationships between Discrete and Dimensional Emotion Models in Affective Picture Databases Using Unsupervised Machine Learning

Abstract: Digital documents created to evoke emotional responses are intentionally stored in special affective multimedia databases, along with metadata describing their semantics and emotional content. These databases are routinely used in multidisciplinary research on emotion, attention, and related phenomena. Affective dimensions and emotion norms are the most common emotion data models in the field of affective computing, but they are considered separable and not interchangeable. The goal of this study was to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The latter affective ratings were collected from a sample of N = 266 children aged 8-12 years [10]. One of the main important features of the NAPS set as a whole (i.e., with all its extensions) is that it combines a relatively large number of pictures with normative ratings identified according to both dimensional and categorical (discrete) emotion theories [11] compared with other stimuli sets, and it also contains additional multiword semantic descriptions organized into different topics, which are all significant features contributing to the successful construction of stimuli sequences for the elicitation of emotional reactions [7,12].…”
Section: Discussionmentioning
confidence: 99%
“…The latter affective ratings were collected from a sample of N = 266 children aged 8-12 years [10]. One of the main important features of the NAPS set as a whole (i.e., with all its extensions) is that it combines a relatively large number of pictures with normative ratings identified according to both dimensional and categorical (discrete) emotion theories [11] compared with other stimuli sets, and it also contains additional multiword semantic descriptions organized into different topics, which are all significant features contributing to the successful construction of stimuli sequences for the elicitation of emotional reactions [7,12].…”
Section: Discussionmentioning
confidence: 99%
“…Discrete and dimensional emotion models are commonly considered distinct and mutually independent. However, previous studies have shown that it is possible to establish a correlation between data points in both models by employing ML techniques to identify patterns in a multidimensional space that integrates the semantics and emotions of stimulation [23,24].…”
Section: Emotion Modelsmentioning
confidence: 99%
“…Empirical evidence has demonstrated the presence of statistically significant correlations between specific pairs of discrete and dimensional emotions [23]. Similarly, unsupervised ML methods have demonstrated the ability to transform ratings from the discrete emotion space into distinct clusters in the dimensional space for specific pairs of discrete-dimensional emotions [24].…”
Section: Hybrid Nlp Model For Sentiment Analysismentioning
confidence: 99%
“…Moreover, statistical analysis methodologies [42,43] were employed to establish a connection between the two ways of interpreting emotions, such as associating discrete emotion labels with corresponding valence and arousal value pairs. For instance, the emotion label "happiness" may be linked to a specific combination of valence and arousal values.…”
mentioning
confidence: 99%